(untitled) (Ágora de Heterodoxias, 2019)
Insecurity presents itself as one of the primary concerns of civil society, reason why the description of a determined act of delinquency is important in order not to disrupt the image of those that participated in a criminal event or that were involved because of the own cojunture of the case itself. This paper is a result of an extended research based on a police journalistic investigation aroused by the abandonment of the police enforcement −claiming wage increases− which led to the riots in a number of provinces in Argentina. From this conception, we pretend to make a reflection about a particular case − the lootings of december 2013 in Córdoba, Argentina− exposing how the acts of those involved are represented and evaluated, within the concepts of justice and civil insecurity that social media contemplates and promotes. This way, in the following article, a socio-semiotic analysis is made through print screens from Facebook, considering that this event also meant an ‘online war’ among those that commited the lootings and those that took ‘justice by their own hands’.